Effect of Primary Stabilisation on Osseointegration of Implants With Local and Systemic Zoledronic Acid Application - Sokmen, Nurullah; Dundar, Serkan; Bozoglan, Alihan; Yildirim, Tuba Talo; Sokmen, Kevser; Sayeste, Erjeng; Kirtay, Mustafa (Lippincott Williams & Wilkins, 2022)
Primary stabilization (PS) is defined as initial tight fit during the surgical placement of an implant. Tight implant placement is quite difficult in cases where bone quality and quantity are insufficient. Zoledronic acid (ZA) is a powerful bisphosphonate that prevents bone resorption. The aim of this study is to investigate the effect of local and systemic ZA application on osseointegration in titanium implants with and without PS. Male Sprague Dawley rats were divided into 2 main groups, with PS, PS + (n = 24), and without primary stabilisation, PS - (n = 24). These main groups were divided into control (n = 8), 2mg/1 mL local ZA (n = 8) and 0.1mg/kg systemic ZA (n = 8) groups. All of the subjects were sacrificed after a 4-week recovery period. Bone implant connection (BiC) and thread filling (TF) (%) of the samples was analyzed according to the non-decalcified histological analysis method. In terms of BiC percentages and TF, statistically significant differences were found between the groups with and without PS and between the ZA treatment groups (P < 0.05). The common effect of PS and ZA use on the percentage of BIC was found to be statistically significant (P < 0.05). The common effect of PS and acid type on TF was not statistically significant (P < 0.05). Within the limitations of this study, it may be concluded that systemic and local administration of ZA may increase implant osseointegration.
Keywords: Bone; bone implant connection; osseointegration; primary stabilisation; zoledronic acid